Directors’ Self-Dealing And The Companies Act, 1965 - Chen, Vivien J.H. (Journal of Malaysian and Comparative Law, 2019)
In this paper, an examination will be made of the existing provisions of the Companies Act, 1965 which relate to self-dealing by directors. A comparison will be made with current companies legislation of Australia and the United Kingdom. The effectiveness of the Malaysian provisions in deterring directors' abuse of position will be considered, along with measures which may be taken to address the inadequacies of the provisions.